Study of Marketing Mix and Aida Model to Purchasing On Line Product in Indonesia - Hadiyati, Ernani (British Journal of Marketing Studies, 2016)
Marketing is a process within company to create value and build mutual relationship with its customer. Marketing is also a strategy to achieve the mission of organization and company; therefore, they have to be effective and better than their competitor in producing, shipping and communicating consumers’ value to the target market. The aim of this research is to find out and analyze the influence of marketing mix to the AIDA model. Marketing mix and AIDA model influence consumers in purchasing online product. The object of this research is consumer who buy online product, and the number of the sample are 97 customers; the sample is chosen by using accidental sampling. The researcher applies path analysis as data analysis method, and the result of this research shows that marketing mix influences AIDA model. Marketing mix and AIDA model influence directly and indirectly to the consumers in purchasing online product.